Colonial Reports On Pakistan's Frontier Tribal Areas - Edited and Introduced by Nichols, Robert (Karachi Oxford University Press, 2005)
"In 2004, as fighting continued in Iraq and Afghanistan moved towards elections, a third aspect of the 'war on terrorism' involved US pressure on Pakistan to eliminate Taliban remnants and foreign, especially Al Qaeda, militants from the Federally Administered Tribal Areas along the Pakistan-Afghanistan border." "Throughout 2004, Pakistan used political negotiation and military force to crush or disperse militants and Pakistani sympathizers, especially near the town of Wana in South Waziristan. Pakistani tactics, derived from British colonial methods, included negotiating with tribal councils, economic blockades, the destruction of homes, mass arrests, and military attacks." "This short volume reprints two, one-hundred-year-old colonial reports on FATA regions, one on Wana and one on the Adam Khel Afridi homelands located near Peshawar. For generations, governments have tried to understand and control FATA regions. These reports suggest the difficulty that state builders with centralizing ambitions have always had in prevailing against semi-independent communities yet to be fully integrated into wider political, economic and administrative systems."--
Include Map, Tables and Index
Keywords: Pakistan--Federally Administered Tribal Areas -- Pakistan--Khyber Pakhtunkhwa